THE APPLICATION OF ROLE PLAYS AS AN EFFORT TO IMPROVE THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMPN 1 TANAH PUTIH - Putri, Mima; Gultom, Effendi (SOROT, 2013)
This is an action research. In doing this research is neededsome of the data is used to support the success. The data for thisresearch will be collected by giving pre-test, post-test andobservation. In order to get or to collect the data for this study, thewriter has to find the suitable instrument. The instrument used forthe speaking test as description. The students are asked to speakbased on the dialogue given by the teacher. In this speaking, theteacher will observe the students ability in grammar, pronunciation,vocabulary and fluency. In this research the writer involved in everycycle and in collecting the data. The researcher used the Observationsheet and test. The observation sheet is to know the students’speaking ability, a check list is used. The check list is done during theclassroom activities. in doing the check list, the researcher will invitecollaborators to the classroom. The class however, will be handled bythe researcher who is in charge of teaching speaking by using roleplay. The test was given to the student is in oral form. Before the testis given, the researcher gave a pre-test at the beginning of the cycleand post-test at the end of the cycle. So, in this research, the studentsare asked to role play their conversation in front of the class based onthe conversation given. The students’ speaking ability between pretestand post-test in every cycle is increase. The research question wasanswered and the hypothesis is reliable. The use of role play is anaffective technique to improve the students’ speaking ability of thefirst year students of SMP Negeri 1 Tanah Putih in academic year2010/2011. In conclusion, the speaking ability of the first yearstudents of SMP Negeri 1 Tanah Putih before treatment is poor. Butafter getting treatment, the students’ speaking ability becomes good.It means that the speaking ability of the students is increase.